Restructuring the Requirements for Establishing a Company in Adopting a One-Man Company Concept Without Limitation - Susanti, Dyah Octorina; Efendi, A'an (Arena Hukum, 2024)
The acceptance of one-man companies in Indonesian company law marks a step forward but falls short of aligning with the modern concept of such entities, as it contradicts the principle of justice. Unlike contemporary one-man companies, which serve as an alternative to multi-member companies and are not restricted to specific types of limited liability companies, the current Indonesian framework imposes limitations that result in unequal opportunities to establish one-man companies. This study addresses three key issues: the rationale behind adopting certain types of one-man companies, the relationship between these restrictions and the principle of justice and the potential for a more inclusive approach to one-man companies without such restrictions. Through doctrinal legal research and law reform-oriented research, this study reaches three conclusions: First, the acceptance of one-man companies is currently limited to Persero (limited liability company), regional-owned enterprises, village-owned enterprises, capital market companies and micro and small business companies. Each of these types differs from general companies in aspects such as establishment, function, organisational structure and dissolution. Second, limiting one-man companies to certain types of companies creates unequal opportunities for establishing such entities, which contradicts the principle of justice. Third, restructuring the requirements for company establishment should not eliminate the terms of agreement; rather, it should offer individuals the option to establish either a multi-shareholder company based on an agreement or a one-man company.